Pengaruh Penambahan Filler Natrium Sulfat Terhadap Ketahanan Kemasan, Dimensi, dan Cost Saving Pada Produk Jerigen di PT. XYZ - Nurfathiyah, Sheila; Sariski, Mario (Unit Penelitian, dan Pengabdian Masyarakat (UPPM) Politeknik ATI Makassar, 2024)
Plastic jerry cans for kerosene are made of plastic, processed with blow molding technology. The production of jerry cans uses HDPE as the raw material and does not include the use of fillers in its formulation. Research aims to determine the impact of filler usage on product quality, achieve packaging durability that meets company standards, and satisfy customer needs with more cost-efficient methods. In order to meet the desired quality, it is necessary to conduct dimensional testing, packaging durability testing, and cost saving analysis. Based on the dimensional test without the addition of filler, data was obtained that did not meet the standards, while the dimensional test with the addition of filler contained sample data that exceeded company standards. Based on packaging durability tests, both using filler and without the addition of filler, the results obtained passed the test in accordance with company standards, such as the absence of leaks and deformation that could disrupt the stability and durability of the jerry can. Based on experimental data, formulations with added fillers can reduce cost savings by 5% for companies.